Household resilience of women migrant worker sellers of Jamu Gendong [version 3; peer review: 2 approved] - Budiman Achmad; Endah Suhaendah; Sanudin Sanudin; Eva Fauziyah; Ary Widiyanto; Dian Diniyati; Rukmini Nugroho Dewi; Aji Winara; Sri Najiyati; Danarti Danarti; Tri Sulistyati Widyaningsih; Aditya Hani; et al. (F1000Research)
Background The selling of Jamu Gendong (an Indonesian traditional herbal medicine), is closely associated with the informal work of women who migrate to different regions. In Sukoharjo Regency and Wonogiri Regency, Central Java Province, the pressing need to meet household necessities in their places of origin compels women to assume the role of breadwinners. Therefore, this research aimed to identify the livelihood capital and resilience of migrant women selling jamu gendong. Methods The study was conducted in Ciamis Regency, West Java Province, Indonesia, in November 2022, using quantitative and qualitative methods. Primary data were collected through structured questionnaires and in-depth interviews. The sample comprised 51 women selected through snowball sampling and actively involved in selling Jamu Gendong, along with six key individuals from relevant agencies. Results The research findings indicate that the households of migrant women who sell jamu gendong can survive and adapt during their migration to prevent poverty by implementing diverse livelihood strategies. They are the only ones who move without their family members renting a place to live with them. This research has identified various capital sources, including productive age and skills in preparing jamu gendong; physical capital, including road infrastructure, markets, and access to health and education facilities; and natural, social, and financial capital. This research provides an in-depth understanding of women’s roles in family economic resilience, diversification of life strategies, the importance of social capital in migrant networks, economic empowerment through migration, and the influence of cultural values on livelihood strategies. Conclusions The findings contribute to a comprehensive understanding of the resilience demonstrated by migrant women selling jamu gendong. However, further research should be conducted in areas beyond the city center to obtain a holistic view of their resilience.